1994
DOI: 10.1152/jappl.1994.77.1.245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of step length optimization on the aerobic demand of running

Abstract: To assess whether distance runners displaying uneconomical freely chosen step lengths (FCSL) could be trained to shift FCSL toward a more optimal setting, six males and three females who exhibited uneconomical FCSL [mean optimal step length (OSL) = -9.81% of leg length from FCSL; mean change in oxygen uptake (VO2) (FCSL - OSL) = 1.46 ml.kg-1.min-1] comprised an experimental group that completed 15 treadmill sessions (30 min/day, 5 days/wk, 3 wk) of OSL training at individually determined running velocities (2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 0 publications
1
49
1
Order By: Relevance
“…Previous studies which have examined the effect of a fatiguing bout of running on subsequent VO 2 during constant-velocity running have all used faster constant velocities which were 12 km.h -1 (Morgan et al, 1990), a mean of 19.0 km.h -1 (Morgan et al, 1996), and 11.3 and 13.7 km.h -1 (Xu and Montgomery, 1995). It was noted by Morgan et al (1994), that at lower velocities, such as the velocity used in the present study, there appeared to be more variation in VO 2 , i.e., less reliability with repeated measurements, which may partly explain the choice of the higher velocities in other studies. The choice of higher velocities may also be due to the similarity between these velocities and the velocity at which the subjects race and train.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies which have examined the effect of a fatiguing bout of running on subsequent VO 2 during constant-velocity running have all used faster constant velocities which were 12 km.h -1 (Morgan et al, 1990), a mean of 19.0 km.h -1 (Morgan et al, 1996), and 11.3 and 13.7 km.h -1 (Xu and Montgomery, 1995). It was noted by Morgan et al (1994), that at lower velocities, such as the velocity used in the present study, there appeared to be more variation in VO 2 , i.e., less reliability with repeated measurements, which may partly explain the choice of the higher velocities in other studies. The choice of higher velocities may also be due to the similarity between these velocities and the velocity at which the subjects race and train.…”
Section: Discussionmentioning
confidence: 52%
“…The results of previous studies have identified a number of biomechanical variables that relate to running economy, including stride length that is freely chosen (11,13,14,38,42,54), low vertical oscillation of body center of mass (13,54), and low peak ground reaction forces (54,55). In this study, we considered the basic biomechanical characteristics most often reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The most striking and ubiquitous finding regarding stride length and running is that a freely chosen stride length is most economical (12,24,38,42,55). Experimentally induced deviations from this freely chosen stride length have invariably evoked increased oxygen cost (14,24).…”
Section: Discussionmentioning
confidence: 99%
“…Runners, coaches, and health professionals are always searching for ways to reduce the risk of injury in runners and improve running economy (RE), which is defined as the aerobic demand (oxygen consumption) of running at a given submaximal speed (Morgan et al, 1994;Saunders, Pyne, Telford, & Hawley, 2004). In this regard, some have experimented with different FSPs.…”
Section: Introductionmentioning
confidence: 99%
“…Although FSA has been reported in previous gait analysis studies, the effect that SR has on specific FSPs (i.e., FFS, MFS, RFS) were not discussed, and it is unclear if a shift in FSP took place as a result of increases and decreases in SR from the participants' preferred SR. Many have used SR conditions or equivalent stride length conditions of ±5% and ±10% from preferred to examine the effects of increases and decreases on a runner's gait (Cavanagh & Williams, 1982;Clarke et al, 1985;Heiderscheit et al, 2011;Morgan et al, 1994). However, previous research seems to be lacking the specific SR parameters required to see a shift in FSP, as well as the coupled effects of SR and FSP on RE in a novice runner population.…”
Section: Introductionmentioning
confidence: 99%